The Contribution of the Mining Sector to the Economic and Social Development of Mongolia - Avirmed, Davaasuren; Bold, Khishigjargal (Mongolian Journal of International Affairs, 2024)
The economic and social development of Mongolia is highly dependent on global market conditions, international economic trends, and the environment for foreign investment. The country’s economic growth has primarily relied on the production of the mining and mineral resources sector. The mining sector occupies a significant position in Mongolia’s industrial production. Furthermore, mining and extractive industries make a substantial contribution to tax revenues in Mongolia's unified state budget. Export revenues from products such as copper concentrate, coal, iron ore, and fluorspar play a vital role in funding the state budget. Over the past decade, the share of the mining sector in GDP, unified state budget revenues, and total exports has increased, while its share in industrial production and total imports has shown a declining trend. These changes have been influenced by unfavorable global economic conditions, declining prices of mineral resources in international markets, and factors such as the COVID-19 pandemic. Except for copper concentrate, Mongolia predominantly exports raw mining products without further processing. Therefore, to implement the goals outlined in the country's long-term development policy, “VISION-2050”, the government needs to take more resolute and consistent measures to process mining products domestically.